PENGARUH PERCEIVED USEFULNESS DAN PERCEIVED EASE OF USE TERHADAP BEHAVIOUR INTENTION TO USE BRI DIGITAL BANKING PADA AGEN BRILINK PT BANK RAKYAT INDONESIA TBK KANTOR CABANG MAGELANG - Wijayanti, Mentari Wilis; Suddin, Alwi; Sutarno, Sutarno (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2019)
This study purpose to determine the significant effect between perceived usefulness towards behavioral intention to use, perceived ease of use towards behavior intention to use, perceived usefulness and perceived ease of use simultaneously and together towards behavioral intention to use BRI digital banking at BRILink agents of PT Bank Rakyat Indonesia, Tbk Magelang branch office with 121 people as sample. The results of multiple linear regression analysis are obtained the results of the validity test is perceived usefulness, perceived ease of use, and behavioral intention to use was valid. Reliability test results show reliable, multicollinearity, heteroscedasticity, autocorrelation, normality test passed the test. Conclusion of the study perceived usefulness has effect towards behavioral intention to use BRI Digital Banking, perceived ease of use has effect towards behavior intention to use of BRI digital banking, perceived usefulness and perceived ease of use simultaneously and together has effect towards behavior intention to use BRI digital banking.